High Protein Intake in Critically Ill Malnourished Ventilated Patients - Farouk Mostafa Faris; Yasmin Nabil Ellithy; Mohamed Amr Matar; Alia Hassan Abd Elfattah (Egyptian Journal of Critical Care Medicine)
Abstract Background Intensive care unit (ICU) patients are at high risk of morbidity, mortality, and prolonged care that need implementing practical approaches to improve outcomes during the early phase of critical illness. When energy and protein are delivered efficiently, this risk is ameliorated and recovery potentially improved. Objective To compare the effect of higher protein intake (1.5 g/kg/day) with standard one (1 g/kg/day) in ICU settings using whey protein during the early phase of the patients’ critical illness and its impact on laboratory and clinical outcomes. Methods This prospective interventional nonrandomized control study was conducted on 40 patients with respiratory failure; all patients were intubated and mechanically ventilated for at least 3 days. Twenty malnourished patients according to the Nutrition Risk in Critically ill (NUTRIC) score received higher protein intake using whey protein, with daily follow-up of blood sugar level, serum electrolytes, and chemistry. ICU outcomes regarding food intolerance, 30-day mortality, length of mechanical ventilation (MV), and ICU stay were recorded. Results This study was conducted on two groups of patients with the same caloric intake and no significant difference regarding demographic and clinical data. High protein intake led to a significant reduction in blood sugar level during first 2 days of ICU stay (P-value = .035 and .048, respectively), with a significant reduction in MV duration (P = .045), reintubation rate (.03), and ICU stay (.02). Conclusion Unlike standard protein diet (1 g/kg/day), higher protein diet (1.5 g/kg/day) in previously malnourished patients was associated with improved glycemic control and serum electrolytes (sodium, potassium, calcium, phosphorus, and magnesium) during their ICU stay with a significant reduction in length of MV and ICU stay.